Switchable Wideband Metamaterial Absorber and AMC reflector for X-band Applications and Operations - M. M. Gajibo; M. K. A. Rahim; N. A. Murad; O. Ayop; H. A. Majid (Universitas Ahmad Dahlan, 2018)
A single layered metamaterial structure with capabilities of switching from a wideband metamaterial absorber to an AMC reflector and vice versa is presented in this paper. A flame retardant 4 substrate with physical thickness of 1.60mm was used. The absorption rate, reflection rate, reflection phase and surface current distribution were studied and discussed. The operational incidental wave angles were varied from 0o to 65o. A peak reflection of about 90% was achieved at 11.20 GHz with a usable bandwidth (-90 to +90) of 3.01 GHz by the AMC reflector. The metamaterial absorber demonstrated a wideband performance (from 8.10 GHz to 14.30 GHz). It achieved 100% absorption at 11.20 GHz and not less than 65